E-Commerce Papua Tani sebagai Marketplace Hasil Pertanian Distrik Skanto Kabupaten Keerom Papua - Mingsep Rante Sampebua; Ign Joko Suyono (Universitas Muhammadiyah Semarang, 2022)
The purpose of the service activity is to implement an online business model, namely e-commerce Papua tani as a marketplace or agricultural products in Keerom Regency. E-commerce Papua tani is a sustainable business model because e-commerce Papua tani can be developed for various business services which include online marketing services, agricultural fertilizer and pharmaceutical services, online marketing agents, business capital for farmers through cooperatives, and extension services, agriculture in partnership with the Keerom Regency Government. The implementation of community service activities is using the lecture method, discussion, question and answer, demonstration, and practice of using the e-commerce Papua tani application. The result of the service activity is the web-based application as a marketplace or agricultural products in the Skanto Disacetrict, Keerom Regency. The e-commerce Papua tani application is used as a medium for the promotion and marketing of farmers' products in the Skanto District which can be marketed online directly to consumers at the right price without going through middlemen. This can increase the income and welfare of farmers in the Skanto District, Keerom District. The implementation of the Papua Tani e-commerce application using tokopedia.com business platform makes it easy for people to sell agricultural products in the Skanto district, Keerom Regency.